Uses of 360° video in referees' reflectivity training: Possibilities and limitations - Boyer, Simon; Rochat, Nadège; Rix-Lièvre, Géraldine (Frontiers in Psychology, 2023)
A pedagogical innovation supported by an online device using 360°video had been conceived to train young soccer and rugby referees to be more reflective. The objective of this exploratory research is to investigate the ways young student referees use the 360°videos in allo-confrontation when carrying out some exercises involving open questions about their viewing experience. A grounded analysis of the student referees’ answers enabled to identify their main focuses when viewing the 360° videos but also to distinguish different cognitive stances. The grounded analysis revealed: (1), idiographic differences between student referees in the video sequencing although the participants seemed to share the same reference points (2) two kinds of focus, one on the unfolding of the game and another one on the referee peer’s activity, and (3) different perspectives according to which student referees use video and to initiate a reflection on a differentiation of several types of immersion: empathic, simulation, exploratory. These results lead to draw some perspectives for the evolution of 360° video supports to design training courses for referees.